Stek Pucuk Kentang (Solanum tuberosum L.) Kultivar IPB CP1 Dapat Menghasilkan Umbi G0 di Dalam Rumah Kaca dan Rumah Kasa di Dataran Menengah: Shoot Cuttings of Potato Plant (Solanum tuberosum L.) Cultivar IPB CP1 Can Produce G0 Tubers in Greenhouses and Screen Houses in the Med-Altitude Area - Tjahjoleksono, Aris; Fatimah, Anggi Siti; Miftahudin (Jurnal Sumberdaya Hayati, 2024)
IPB CP1 potato is a raw material for potato chips. The advantage of IPB CP1 potatoes is their high yield. Challenges in potato production are limited areas with optimal altitude and condition as well as low quality and quantity of seeds. Utilizing a mid-altitude area for potato cultivation is one of the solutions to increase potato seed production. This study aimed to compare the growth and production of IPB CP1 G0 seed tuber in a greenhouse and screenhouse in mid-altitude with different numbers of shoot cuttings per polybag. This research was conducted with two factors. The first factor is the use of growth plant houses, i.e. greenhouse and screenhouse. The second factor is the number of shoot cuttings per polybag, i.e. 2 and 3 shoot cuttings per polybag. Growth parameters observed included plant height, number of nodes and leaves, and fresh and dry weight of shoots. The production parameters observed included the number as well as fresh and dry weight of tubers. The growth and production of IPB CP1 potatoes grown in the greenhouse were better than those grown in the screenhouse. The number of cuttings per polybag did not affect the growth and production of IPB CP1 potato.